2021
DOI: 10.9734/arrb/2021/v36i330353
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Diversity Analysis of Somaclonal Variants of Potato (Solanum tuberosum L.) by Random Amplified Polymorphic DNA Markers

Abstract: Aims: An experiment was conducted to analyze the DNA fingerprinting and genetic diversity of nine potato (Solanum tuberosum L.) somaclonal variants and three check varieties. Place and Duration of Study: The experiment was carried out at the Biotechnology laboratory of the Department of Biotechnology, Faculty of Agriculture, Sher-e-Bangla Agricultural University, Dhaka-1207, Bangladesh during November, 2013 to December, 2014. Methodology: The somaclonal variants investigated were SIP-3, SIP-5, SVP-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Here, Sheel Bilati and SAU Promising Genotype-5 genotype pairs are more closely related than other genotype pairs. Likewise, Brenna (2004) andShamsuzzaman et al (2021) showed the genetic relationship among 12 potatogenotypes with similar dendrogram.…”
mentioning
confidence: 81%
See 3 more Smart Citations
“…Here, Sheel Bilati and SAU Promising Genotype-5 genotype pairs are more closely related than other genotype pairs. Likewise, Brenna (2004) andShamsuzzaman et al (2021) showed the genetic relationship among 12 potatogenotypes with similar dendrogram.…”
mentioning
confidence: 81%
“…Seven decamer primers of random sequence viz. OPA-17, OPA-18, OPB-06, OPB-09, OPC-01, OPF-08 and OPW-01 (Operon Technologies, Inc., Alameda, California, USA; Pattanayak et al, 2004;Shamsuzzaman et al, 2021) were initially screened on 10 potato genotypes and the best five (OPA-18, OPB-06, OPC-01, OPD-02 and OPW-01) were selected based on their ability to produce polymorphic DNA band.…”
Section: Primer Selectionmentioning
confidence: 99%
See 2 more Smart Citations